Design of Dual Band Microstrip Antenna at L-Band and S-Band Frequencies for Synthetic Aperture Radar (SAR) Sensors - Binarti Fauziah Fitriani; Heroe Wijanto; Agus Dwi Prasetyo (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
Synthetic Aperture Radar (SAR) is a remote sensing system using radar for high resolution image capture. The higher frequency used, the higher accuracy of the image detail that obtained, while, the lower frequency has a better image penetration capabilities. To combine these two advantages of the image result characteristic, SAR is designed to operate in two bands (dual-band). In this study, a dual-band antenna on 1.27 GHz (L-Band) and 3 GHz (S-Band) using slotted patch technique and proximity coupled feeding is designed. The material that used is the FR4 Epoxy dielectric with the relative permittivity of 4.6. As a result, the antenna operates at the frequency of 1.27 GHz with the return loss of -25.131 dB, VSWR 1.1201, and 19.9 MHz (return loss <= -10 dB) bandwidth. While the return loss of 3 GHz is -16.802 dB, VSWR 1.3381, and bandwidth (return loss <= -10 dB) 125.3 MHz